Society of Mind cognitive agent architecture applied to drivers adapting in a traffic context. (April 2014) - Leu, George; Curtis, Neville J; Abbass, Hussein A
This paper challenges the idea of creating an architectural approach for designing a complex hybrid cognitive agent, i.e., an agent that possesses all reactive, deliberative and affective capabilities, outside the hierarchical paradigm. Thus, it presents an agent architecture based on Marvin Minsky's 'Society of Mind' (SoM) metaphor on human mind and cognition, and shows how SoM agents, through the features implicitly generated by their design, allow a tremendous power of representation of human heterogeneity and variety of behaviours. In order to show that, the SoM general architecture is instantiated and evaluated in a cognitively demanding environment: as a driver agent in a traffic behaviour context.